Downregulation of keratins 8, 18 and 19 influences invasiveness of human cultured squamous cell carcinoma and adenocarcinoma cells - UCHIUMI, A. (D.A. Spandidos, 2012)
Keratin (K) expression index has been reported to be related to cell invasion activity in adenocarcinoma. In a previous study, we observed a negative correlation between K expression and cell invasion activity; i.e., when many Ks are expressed in the cells, the cell activity is low. To further elucidate the correlation between Ks and invasion activity, RNA interference experiments of K8, K18 and K19 were carried out to clarify the essential role of Ks using T24 and HEC-1 as typical squamous cell carcinoma and adenocarcinoma cells, respectively. K8 small interfering RNA (siRNA) was most effective against K18 and K19 expression and demonstrated the strongest effect on relative invasion activity among the siRNAs used. These results suggest that K8/K18 or K8/K19 filaments may play roles in internal cell structure and invasion activity. Moreover, K18 and K19 were capable of substituting for each other, and K18 or K19 formed filaments with K8. In addition, cells treated with K8 siRNA demonstrated high invasion activity, which was approximately double that observed with control siRNA in HEC-1 cells. The order of effects was K8>K19>K18 in the two cell lines. The above results suggest that K8 may play a signifiant role in invasive functions in epithelial and metastatic cells.